Vanishing of negative #1#1#1=≤ ==≥ =PrFrReK-theory in positive characteristic. (17th July 2014) - Kelly, Shane
Abstract: We show how a theorem of Gabber on alterations can be used to apply the work of Cisinski, Suslin, Voevodsky, and Weibel to prove that K_n(X) Z[1/p]= 0 for n < -\! X where X is a quasi-excellent noetherian scheme, p is a prime that is nilpotent on X, and K_n is the K -theory of Bass–Thomason–Trobaugh. This gives a partial answer to a question of Weibel.